Ligands of the Peripheral Benzodiazepine Receptor Are Potent Inhibitors of Plasmodium falciparum and Toxoplasma gondii In Vitro - Dzierszinski, Florence (American Society for Microbiology, 2002)
The increase in resistance of the malaria parasite Plasmodium falciparum to currently available drugs demands the development of new antimalarial agents. In this quest, we have found that ligands to the peripheral benzodiazepine receptor such as flurazepam, an agonist of the benzodiazepine family, and PK11195, an antagonist derived from isoquinoline, were active against Plasmodium falciparum. These two compounds effectively and rapidly inhibited parasite growth in vitro, irrespective of parasite resistance to chloroquine and mefloquine. Treatment with both drugs induced a sharp and consistent decline in parasitemia, a complete inhibition of parasite replication, and the destruction of parasites within the host red blood cells. Using electron microscopy, we showed that dramatic morphological changes, involving swollen endoplasmic reticulum and the reduction of hemozoin, were consistent with parasite death. The potent activities of flurazepam and PK11195 were also evaluated for antagonist or synergistic effects with currently used antimalarial drugs such as chloroquine and mefloquine. Moreover, flurazepam was found to be active against Toxoplasma gondii, another member of the phylum Apicomplexa. Taken together, our results indicated that benzodiazepines could be considered promising candidates in the treatment of both malaria and toxoplasmosis.